6t-5=2t-5

Simple and best practice solution for 6t-5=2t-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6t-5=2t-5 equation:


Simplifying
6t + -5 = 2t + -5

Reorder the terms:
-5 + 6t = 2t + -5

Reorder the terms:
-5 + 6t = -5 + 2t

Add '5' to each side of the equation.
-5 + 5 + 6t = -5 + 5 + 2t

Combine like terms: -5 + 5 = 0
0 + 6t = -5 + 5 + 2t
6t = -5 + 5 + 2t

Combine like terms: -5 + 5 = 0
6t = 0 + 2t
6t = 2t

Solving
6t = 2t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-2t' to each side of the equation.
6t + -2t = 2t + -2t

Combine like terms: 6t + -2t = 4t
4t = 2t + -2t

Combine like terms: 2t + -2t = 0
4t = 0

Divide each side by '4'.
t = 0

Simplifying
t = 0

See similar equations:

| 266-6x=39x+21 | | 3r+6=18 | | 7x(-2x+3)=0 | | 6x(4x+3)=0 | | 2(2)-3y=-9 | | -50+x=-10 | | 40x-6=9 | | -4(x+3)=x+8 | | 6x(4x-1)=0 | | 5x-10x=x-12 | | 172-6x=6x+16 | | -(-2x)=(-88) | | 2(x+4)=5x-1 | | 6p+12=4p | | -4x+12=x+17 | | 12-9x=52-16x | | 3x-7=-4x | | 3x-7=-1 | | -x-6=-2 | | (x^2-9)(x+4)=0 | | 18+x=-2 | | X^4+6x=0 | | 5x-7=103 | | (x^2-2)(x^2+3)=0 | | 170-5x=6x+5 | | 5x+1=3x+13 | | -4x^2-4x+3=0 | | 6p+3=3p+12 | | q=4.5-0.5 | | P^2-6p+8= | | 5x-2=x-14 | | 58-5=8+19 |

Equations solver categories